Given: s i n ( x ) + c o s ( x ) = 2 1 And s i n 3 ( x ) + c o s 3 ( x ) = b a
Find: b − a such that a and b are co-prime integers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given:
sin ( x ) + cos ( x ) = 2 1
Square both sides
[ sin ( x ) + cos ( x ) ] 2 = ( 2 1 ) 2
Factor out
sin 2 ( x ) + 2 sin ( x ) cos ( x ) + cos 2 ( x ) = 4 1
But
sin 2 ( x ) + cos 2 ( x ) = 1
So
2 sin ( x ) cos ( x ) + 1 = 4 1
Simplify (Eq. 1)
sin ( x ) cos ( x ) = − 8 3 E q . ( 1 )
Cube given equation
[ sin ( x ) + cos ( x ) ] 3 = ( 2 1 ) 3
Factor out
sin 3 ( x ) + 3 sin 2 ( x ) cos ( x ) + 3 sin ( x ) cos 2 ( x ) + cos 3 ( x ) = 8 1
Separate
sin 3 ( x ) + cos 3 ( x ) = 8 1 − 3 sin 2 ( x ) cos ( x ) − 3 sin ( x ) cos 2 ( x )
Factor out right side
sin 3 ( x ) + cos 3 ( x ) = 8 1 − 3 sin ( x ) cos ( x ) [ sin ( x ) + cos ( x ) ]
Plugin given equation and Eq. 1
sin 3 ( x ) + cos 3 ( x ) = 8 1 − 3 ( − 8 3 ) ( 2 1 ) = 1 6 1 1 = b a
∴ a = 1 1 a n d b = 1 6
b − a = 1 6 − 1 1 = 5
Nice factoring at the end of the equation.
Problem Loading...
Note Loading...
Set Loading...
Sum of Two Cubes: sin 3 x + cos 3 x = ( sin x + cos x ) ( sin 2 x − sin x cos x + cos 2 x ) First, note that from the first equation you get: ( sin x + cos x ) 2 = 2 1 2 1 + 2 sin x cos x = 4 1 sin x cos x = − 8 3 Now we have everything we need, we just need to substitute these values to the first equation: ( sin x + cos x ) ( sin 2 x − sin x cos x + cos 2 x ) ( 2 1 ) ( 1 + 8 3 ) = 1 6 1 1 And so, b − a = 1 6 − 1 1 = 5